Bridging Digital Justice: A Comparative Study of E-Commerce Arbitration in Indonesia and Taiwan - Asyiqin, Istianah Zainal; Fitriyanti, Fadia; Yunita, Ani; Akbar, M. Fabian; Pei-Fen, Tsai (Lex Scientia Law Review, 2025)
The rapid expansion of e-commerce has significantly altered the global trade landscape, presenting legal challenges and opportunities, particularly in cross-border transactions. Arbitration has emerged as an effective mechanism for resolving e-commerce disputes, due to its enforceability and flexibility. The intersection between arbitration and e-commerce necessitates immediate attention as electronic signatures, digital contracts, and remote proceedings become more common. This study employed a normative legal approach to evaluate the arbitration frameworks of Indonesia and Taiwan in the context of e-commerce disputes. While Law No. 19 of 2016 on Electronic Information and Transactions (ITE Law) supports Indonesia's legal system, it lacks specific provisions on arbitration for digital commerce, particularly in international contexts. In contrast, Taiwan exhibits a more comprehensive system integrating its Electronic Signatures Act with arbitration practices, enabling a more significant adaptation to technological advancements. While Taiwan's Arbitration Act does not explicitly regulate remote hearings, the Code of Civil Procedure and Judicial Yuan's pertinent regulations permit remote hearings, video conferencing, and electronic evidence submission, thereby guaranteeing continuity and efficiency, particularly during the COVID-19 pandemic. According to this investigation, Taiwan's institutional and procedural preparedness for digital dispute resolution is more advanced. To augment its e-commerce arbitration skills, Indonesia must integrate digital technologies and address regulatory gaps within its arbitration system. The comparative research provides a distinct viewpoint on how both nations might mutually benefit from enhancing legal clarity, effectiveness, and cross-border enforceability within the digital economy.